The Job Characteristics of Industrial Salespersons: Relationship to Motivation and Satisfaction - Becherer, Richard C. and Morgan, Fred W. and Richard, Lawrence M. (Journal of Marketing, 1982)
The job characteristics model of worker motivation has been applied in many organizational settings. An empirical application of this model to the industrial sales position is presented in this article. The model appears to have potential in the study of sales force motivation and satisfaction.
https://katalog.adlr.link/Record/ai-55-aHR0cHM6Ly93d3cuanN0b3Iub3JnL3N0YWJsZS8xMjUxMzY4